Two Cases of Influenza B Virus-Related Fatal Fulminant Pneumonia Complicated With Staphylococcus aureus Infection in China Diagnosed Using Next-Generation Sequencing (2018) - Bai, Bing; Wang, Hongyan; Li, Meng; Ma, Xiaoyu; Zheng, Jinxin; Deng, Qiwen; Yu, Zhijian (Frontiers in Public Health, 2020)
Two rare cases of Chinese female patients with influenza B virus infection complicated with both fulminant pneumonia and septicemia caused by Panton–Valentine leukocidin(PVL) positive methicillin-sensitive Staphylococcus aureus (MASS) were reported for the first time in China through next-generation sequencing (NGS). An increasing body of evidence indicates that co-infection with influenza B virus and bacterial pneumonia is often fatal. Rapid and precise identification of the co-infection bacteria can guide the selection of treatment for patients with influenza virus infection in the clinical setting. In this study, next-generation sequencing (NGS) was applied for the rapid diagnosis of these two cases. Despite the unfavorable survival outcome of these patients, the application of next-generation sequencing showed promise as a diagnostic tool for the rapid diagnosis of unknown pathogens in patients with bacterial pneumonia and sepsis. This method can guide the administration of medications in such patients.